2023
DOI: 10.3390/agronomy13040955
|View full text |Cite
|
Sign up to set email alerts
|

Development of Integrated Farming System Model—A Step towards Achieving Biodiverse, Resilient and Productive Green Economy in Agriculture for Small Holdings in India

Abstract: The agrarian communities of South Asia are dominated by small and marginal farmers (<2.0 ha operational holdings) and are confronted with manifold challenges of lower productivity, income, and resource degradation. For optimized and efficient resource use, a shift from business as usual towards green economy is imperative. Therefore, a study to address these challenges, through integrating diverse crops and allied enterprises under an integrated farming system (IFS) model was carried out. We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…An integrated farming system (IFS) is a mixed farming approach that combines crop and livestock activities in a mutually beneficial manner [19,20]. The objective is to implement a set of practices for resource development and utilization that results in significant and sustained increases in agricultural production and farm income [21].…”
Section: Brief Overview Of the Economics Of Integrated Farming Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated farming system (IFS) is a mixed farming approach that combines crop and livestock activities in a mutually beneficial manner [19,20]. The objective is to implement a set of practices for resource development and utilization that results in significant and sustained increases in agricultural production and farm income [21].…”
Section: Brief Overview Of the Economics Of Integrated Farming Systemsmentioning
confidence: 99%
“…Channabasavanna et al [40] developed a rice-fish-poultry system for rice-growing farmers in Karnataka, India, and found that the designed system exhibited the highest productivity, with a 26.3% increase compared to the conventional rice-rice system. Despite the numerous benefits of the IFS, some integrated systems require more money, labor, and other resources to initiate and maintain [19,20,23,[41][42][43]. For instance, Manjunath and Itnal [27] observed that integrating dairy production with coconut through forage intercropping increased net returns nearly fivefold compared to a monocropping system, but the production cost of the integrated system also increased by fivefold.…”
Section: Brief Overview Of the Economics Of Integrated Farming Systemsmentioning
confidence: 99%
“…Energy use efficiency (Fatima et al, 2023), economic returns, and environmental sustainability (Shyam et al, 2023) of agriculture enterprises are greatly influenced by the quantum and form of energy used in a cropping system. A production system with comparatively lower input requirements and higher outputs is the most efficient one (Upadhyay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%